HUBUNGAN INFEKSI HUMAN PAPILLOMA VIRUS (HPV) DENGAN KEJADIAN KANKER SERVIKS - Surmanto, Boy; Lumbanraja, Alex M.; Fauzi, Tengku Muhammad (Universitas Methodist Indonesia, 2021)
Background: One of the most common malignancies among women around the world is cervical cancer. Cervical cancer is a multifactorial disease, one of the risk factors include infection with the HPV virus, with type 16 and type 18 as the most common type associated with cervical cancer. This study aims to investigate the relationship between cervical cancer with Human Papilloma Virus infection. Methods: This literature review obtained was conducted through searching the medical research journals that have been published in online journals both nationally and internationally using Google Scholar with keywords: cervical cancer, human papillomavirus infection. The literatures included in this literature review were Indonesian and English literatures published in the last 5 years starting from 2013 to 2018. Results: Six literatures addressing the relationship between the incidence of cervical cancer and HPV infection were found from the literature searching. These literatures were published from 2013 to 2018. Three of the literatures were case-control studies while the other three were cross-sectional studies. Conclusion: Human papilloma virus infection increases the risk of cervical cancer. The HPV types 16 and 18 virus are associated with cervical cancer.